2018
DOI: 10.1371/journal.pbio.2005722
|View full text |Cite
|
Sign up to set email alerts
|

Frontostriatal pathways gate processing of behaviorally relevant reward dimensions

Abstract: The value of rewards arises from multiple hedonic and motivational dimensions. Reward-encoding brain regions such as the ventral striatum (VS) are known to process these dimensions. However, the mechanism whereby distinct reward dimensions are selected for neural processing and guiding behavior remains unclear. Here, we used functional imaging to investigate how human individuals make either hedonic (liking) or motivational (wanting) evaluations of everyday items. We found that the two types of evaluations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 73 publications
7
32
2
Order By: Relevance
“…Although we found activation in regions associated with reward and incentives (Diekhof et al, 2012;Bartra et al, 2013), it is important to be careful with the conclusion that it is "rewarding" to choose negative information (Poldrack, 2006). Reward regions are associated with a multitude of psychological processes (Bartra et al, 2013), and reward is a construct with different dissociable dimensions, including "liking" and "wanting" (e.g., Weber, Kahnt, Quednow & Tobler, 2018;Berridge, Robinson & Aldridge, 2009). In addition, the distributed pattern of activation that we found most likely reflects psychological processes beyond reward as well.…”
Section: Discussionmentioning
confidence: 75%
“…Although we found activation in regions associated with reward and incentives (Diekhof et al, 2012;Bartra et al, 2013), it is important to be careful with the conclusion that it is "rewarding" to choose negative information (Poldrack, 2006). Reward regions are associated with a multitude of psychological processes (Bartra et al, 2013), and reward is a construct with different dissociable dimensions, including "liking" and "wanting" (e.g., Weber, Kahnt, Quednow & Tobler, 2018;Berridge, Robinson & Aldridge, 2009). In addition, the distributed pattern of activation that we found most likely reflects psychological processes beyond reward as well.…”
Section: Discussionmentioning
confidence: 75%
“…Although we found activation in regions associated with reward and incentives, it is important to be careful with the conclusion that it is “rewarding” to choose negative information 42 . Reward regions are associated with a multitude of psychological processes 18 , and reward is a construct with different dissociable dimensions, including “liking” and “wanting” (e.g., 31 , 43 . In addition, the distributed pattern of activation that we found most likely reflects psychological processes beyond reward as well.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the involvement of a subregion of the ventral striatum in the sensory pleasure experience is more striking. fMRI studies conducted in humans have sometimes reported the involvement of the ventral striatum in hedonic reactions ( 21,22 ), but less consistently than the mOFC ( 23 ). Studies conducted in rodents have highlighted the presence of small “hedonic hotspots” in the shell division of the ventral striatum enhancing the hedonic experience when stimulated with opioids, orexin, or endocannabinoid ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to animals, sensory pleasure in humans appears to be modulated by opioidergic activity ( 19 ). However, whereas some studies do find that the magnitude of the experienced sensory pleasure correlates with the activity of the ventral striatum ( 20, 21 ), sensory pleasure has been most consistently reported to correlate with the activity of the medial orbitofrontal cortex (mOFC) rather than the ventral striatum ( 2224 ).…”
Section: Introductionmentioning
confidence: 99%